Discovery of solid bitumen in the Cambrian reservoirs and its geological implications in the Ordos Basin, China - Huang, Junping; Li, Xiangbo; Tan, Kaijun; Xiang, Nijiao; Zhang, Yan (Frontiers in Earth Science, 2023)
This study reports a comprehensive geochemical analysis of several samples of the solid bitumen recently discovered in the Cambrian reservoirs in drillings and outcrops in the Ordos Basin. The results show that the solid bitumen in the reservoir features intergranular pores and micro-fractures, with mineral particle surfaces of dolomite and limestone, and relatively clear and flat boundaries. The D and G peaks in the laser Raman spectrum were prominent. According to distributions of shapes of the D and G peaks as well as the relevant parameters of the laser Raman, the vitrinite equivalent reflectance (Roeq) values were from 2.12% to 3.46% in the solid bitumen. This indicates that the solid bitumen in the reservoirs had undergone significant thermal evolution, and were mainly composed of pyrobitumen. Moreover, it mainly consisted of four types of atoms, C, O, Ca, and Mg, which confirms the hypothesis of the significant thermal evolution of the samples. In addition, the analysis of the origin of the Cambrian natural gas as well as the correlation between the solid bitumen and the potential source rocks show that the solid bitumen in the Cambrian reservoirs of the southern basin had features similar to those of the Lower Cambrian source rocks, except the samples from Well T59. All evidence suggests that the high-abundance source rocks of the Lower Cambrian have made considerable contributions to the Cambrian natural gas and the solid bitumen in the Cambrian reservoirs of the southern basin. The work here provides a new scientific basis for exploring natural gas in the Cambrian and deep strata of the Ordos Basin.